Study on real-time industrial control networks - Wu, Xuepei (2019)
Boosted by business trends such as Industry 4.0, Industrial Internet of Things (IIoT) solutions such as real-time Ethernet and wireless technologies have been increasingly deployed in the industrial automation sector. Higher fluctuation and less predictability in terms of customer demand promoted by Industry 4.0 can be overcome by improving the flexibility of the system via network-based control. However, closing control loops over a shared communication network means that the system performance can be highly dependent on the quality of the communication services which transfer control variables (e.g., set-point and measurement) between controllers, sensors and actuators. It is of great importance to design a common networking solution to meet real-time (and wireless) requirements in networked control systems, and maintain the backward compatibility to distributed control systems where soft real-time communication is sufficient.